2020
DOI: 10.3390/medicina56030123
|View full text |Cite
|
Sign up to set email alerts
|

Perish or Publish Dilemma: Challenges to Responsible Authorship

Abstract: Controversies related to the concept and practice of responsible authorship and its misuse have been among the most prominent issues discussed in the recent literature on research integrity. Therefore, this paper aims to address the factors that lead to two major types of unethical authorship, namely, honorary and ghost authorship. It also highlights negative consequences of authorship misuse and provides a critical analysis of different authorship guidelines, including a recent debate on the amendments of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 38 publications
1
36
0
16
Order By: Relevance
“…endorsement of authorship guidelines by medical journals. Furthermore, implementing a support system to discuss and resolve authorship disputes may also help reduce the proportion of HA [7]. Based on the estimated proportions of HA, attempts should be made by universities, medical journals and individual researchers to further reduce authorship misuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…endorsement of authorship guidelines by medical journals. Furthermore, implementing a support system to discuss and resolve authorship disputes may also help reduce the proportion of HA [7]. Based on the estimated proportions of HA, attempts should be made by universities, medical journals and individual researchers to further reduce authorship misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Another solution might be the referral to and endorsement of authorship guidelines by medical journals. Furthermore, implementing a support system to discuss and resolve authorship disputes may also help reduce the proportion of HA [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this scoping search we concluded that HA merits a systematic review and that no prior systematic reviews seems to have covered this topic. Only 2 earlier reviews were identi ed, but these manuscripts gave narrative reviews on authorship issues [23], publication practices and responsible authorship [24] or systematically reviewed other authorship issues [25]. This research study may help design future studies and bring ideas on how to counteract HA.…”
Section: Review Item 3: Researchers Admitting Being An Honorary Author On a Publicationmentioning
confidence: 99%
“…Por un lado, se mantiene vigente el debate de las últimas décadas: la producción de artículos científicos es criticada y acusada de obedecer a una lógica productivista de la ciencia. Los últimos análisis no sólo indagan sobre esta condición, sino sobre el impacto que puede a tener a nivel de responsabilidad ética en la publicación de los papers (Aliukonis, 2020), y desde luego en la calidad de la información publicada. Se trata de un fenómeno visible países emergentes y con alta productividad (Kwanya, 2018).…”
Section: La Comunicación Científicaunclassified